(untitled) (Texas Journal of Philology, Culture and History, 2025)
Problems related to the human psyche and its inner world in works of art created today are considered a separate issue. In fact, this topic was present in many of our works created in the past. The fact that the fate of women and issues related to their psyche in Abdullah Qahhor’s stories on the theme of the past, "Patient", "Pomegranate", "Headless Man", "Horror", are expressed in a unique way is also proof of our opinion. This article examines the issue of the psyche of the characters in Abdullah Qahhor’s story "Tales from the Past". The content of the events in the story "Hur qiz" presented in this story, the character traits of the characters in it, and the childhood memories of the main character, young Abdullah, are scientifically studied. The writer’s skill has scientifically analyzed the fact that the helplessness, inner mental anguish and tragic fate of Sarviniso, who is his uncle’s daughter, are truthfully revealed. The story presents the events that young Abdullah saw with his own eyes and became a participant in, Sarviniso’s inability to satisfy her desires and wishes as a human being, her engagement to a man who did not like her, The events of his being ignored, living in torment, and being beaten to death by his father are explored through the lens of the writer’s skill.